On the theory of the Beltrami equation
We study ring homeomorphisms and, on this basis, obtain a series of theorems on the existence of the so-called ring solutions for degenerate Beltrami equations. A general statement on the existence of solutions for the Beltrami equations that extends earlier results is formulated. In particular, we give new existence criteria for homeomorphic solutions f of the class W^1, 1_loc with f −1 ∈ f^—1 W^1, 2_loc in terms of tangential dilatations and functions of finite mean oscillation. The ring solutions also satisfy additional capacity inequalities., number=11, journal=Ukrains’kyi Matematychnyi Zhurnal, author=Ryazanov, V. I. and Srebro, U. and Yakubov, E., year=2006, month=Nov., pages=1571–1583